Literary Analysis of Inter-Multidisciplinary Understanding of Islam: Nature, Objectives, and Impacts - Dimas Afditiya Ramadhan; M Nasor; Rini Setiawati (EDUCATIO : Journal of Education, 2024)
The inter/multidisciplinary understanding of Islam represents a comprehensive and inclusive approach to comprehending the religion in an increasingly complex and interconnected world. This study delves into the nature, objectives, and impacts of this approach, aiming to provide a holistic perspective on how Islam can be understood through the integration of various academic disciplines. The primary objectives of this approach include introducing religious values, enhancing the understanding of social and cultural contexts, and formulating solutions for contemporary issues. The study also seeks to illustrate how an inter/multidisciplinary perspective contributes to promoting intercultural tolerance and fostering deeper critical thinking. This paper employs a literary analysis method, synthesizing insights from disciplines such as social sciences, humanities, economics, and political science to develop a more nuanced understanding of Islam. The analysis draws from a wide range of academic literature and case studies. The findings reveal that an inter/multidisciplinary approach to understanding Islam offers profound insights and broad objectives that extend beyond traditional religious knowledge. This approach enables a comprehensive understanding of Islam within a broader context, addressing contemporary challenges such as social justice, cultural tolerance, and global interconnectedness. The study concludes that an inter/multidisciplinary understanding of Islam is a crucial instrument for individuals to become active agents of change, playing a vital role in shaping a tolerant, just, and harmonious society. This approach is essential for creating inclusive and equitable societies, bridging the gap between tradition and contemporary realities, and building a world that respects diversity, promotes peace, and realizes justice. Therefore, this approach brings extraordinary positive impacts in addressing the challenges of our time.